Cancer management in the Pacific region: a report on innovation and good practice. Issue 9 (September 2019) - Ekeroma, Alec; Dyer, Rachel; Palafox, Neal; Maoate, Kiki; Skeen, Jane; Foliaki, Sunia; Vallely, Andrew J; Fong, James; Hibma, Merilyn; Mola, Glen; Reichhardt, Martina; Taulung, Livinston; et al.
Summary: Pacific island countries and territories (PICTs) face the challenge of a growing cancer burden. In response to these challenges, examples of innovative practice in cancer planning, prevention, and treatment in the region are emerging, including regionalisation and coalition building in the US-affiliated Pacific nations, a point-of-care test and treat programme for cervical cancer control in Papua New Guinea, improving the management of children with cancer in the Pacific, and surgical workforce development in the region. For each innovation, key factors leading to its success have been identified that could allow the implementation of these new developments in other PICTs or regions outside of the Pacific islands. These factors include the strengthening of partnerships within and between countries, regional collaboration within the Pacific islands (eg, the US-affiliated Pacific nations) and with other regional groupings of small island nations (eg, the Caribbean islands), a local commitment to the idea of change, and the development of PICT-specific programmes.